Experimental Research on Unit Operation for Fruit Crops’ Bones Calibration - Larysa Bondarenko; Serhii Halko; Oleksandr Matsulevych; Illia Tetervak; Oleksandr Vershkov; Oleksandr Miroshnyk; Vitalii Nitsenko; Valerii Havrysh (Applied Sciences, 2022)
The article presents the results of the implementation of the mathematical planning of the experiment to determine the optimal parameters of the calibration process of cherry, sweet cherry, cherry plum, apricot and almond seeds. The essence of this process is the separation of seeds (bones) of fruit crops into fractions homogenous in size in order to highlight the middle fraction, which is about 80% of the total number of bones. The bones of the middle fraction are of the highest quality and are most suitable for sowing. The shape of the bones was evaluated by three parameters: length, width, and height. Calibration was performed according to the width of the bone. To carry out experimental studies, a calibration device was developed, the working body of which is the sieve part. Ball cleaners were used to prevent clogging of the perforated sieve. A mathematical theory of experimental planning was used. The criterion of optimization for all fruit crops was taken as an indicator of the quality of bone division into homogeneous fractions. The functional dependence of this indicator on the frequency and amplitude of oscillations of the grating part of the calibration unit, as well as on the angle of inclination of the sieves, was investigated. To implement the experimental data, we used a rotatable Boks plan of the second order. Regression models of the cherry, sweet cherry, cherry plum, apricot, and almond calibration process were obtained. Adequacy of the models was assessed by Fisher’s criterion. As a result, the optimal operating parameters of the installation were determined. This ensures the qualitative separation of the bones of fruit crops into homogeneous fractions with a mass deviation of up to 7%. An assessment of the quality of work of ball sieve cleaners was carried out. To do this, we used the coefficient of efficiency of the live cross-section. With the optimal parameters of the installation, the value of this coefficient of the unit for all fruit crops is within 0.87 to 0.95. This indicates that the calibration process is of high quality.